1988
DOI: 10.1557/proc-127-489
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Leachability of MLW Stream Containing Cr, Ni and Cd Immobilized in a Cement Matrix

Abstract: Cement samples containing variable amounts of Cr(III) or Ni(II) or Cd(II) as chloride admixtures present in a MLW stream from reprocessing of spent fuel were prepared under established procedure. Due to the high pH generated in the cement clinker hydration, respective metal hydroxides are formed and improve the physical characteristics of the cement matrix. An increase in the value of the compressive strength was observed when about 7% of the above elements were blended in cement. The increase depends on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The two principal constituents of most commercial fixing agents are cementitious materials (Portland cement, fly ash, lime and sodium carbonate) but a combination of cement and soluble silicates was found to be best binder in the solidification of a largely inorganic residue with trace concentrations of organic contaminants [93]. Many researchers studied the effect of heavy metals on solidification of cement [94][95][96][97][98][99].…”
Section: Fixation Of Heavy Metals In Portland Cementmentioning
confidence: 99%
“…The two principal constituents of most commercial fixing agents are cementitious materials (Portland cement, fly ash, lime and sodium carbonate) but a combination of cement and soluble silicates was found to be best binder in the solidification of a largely inorganic residue with trace concentrations of organic contaminants [93]. Many researchers studied the effect of heavy metals on solidification of cement [94][95][96][97][98][99].…”
Section: Fixation Of Heavy Metals In Portland Cementmentioning
confidence: 99%
“…Wang & Vipulanandan (2000) concluded that addition of Cr(VI) in the form K 2 CrO 4 extended the initial and final setting time and decreased the compressive strength. Zamorani et al (1989) discovered that low Cr(III) levels in cement system accelerated the setting time. Pera et al (1997) notified that the immobilization of Cr(VI) by hydraulic binders takes place by one or a combination of the following mechanisms: addition, substitution or precipitation of new components.…”
Section: Introductionmentioning
confidence: 99%